Contributing or free-riding? A theory of endogenous lobby formation - Taiji Furusawa; Hideo Konishi (Fondazione Eni Enrico Mattei (FEEM), 2008)
We consider a two-stage public goods provision game: In the first stage, players simultaneously decide if they will join a contribution group or not. In the second stage, players in the contribution group simultaneously offer contribution schemes in order to influence the government's choice on the level of provision of public goods. Using perfectly coalition-proof Nash equilibrium (Bernheim, Peleg and Whinston, 1987 JET), we show that the set of equilibrium outcomes is equivalent to an 'intuitive' hybrid solution concept, the free-riding-proof core, which is always nonempty but does not necessarily achieve global efficiency. It is not necessarily true that an equilibrium lobby group is formed by the players with highest willingness-to-pay, nor is it a consecutive group with respect to their willingnesses-to-pay. We also show that the equilibrium level of public goods provision shrinks to zero as the economy is replicated.
Keywords: C71; C72; F13; H41; 330; Common Agency; Public Good; Free Rider; Core; Lobby; Coalition Formation; Coalition-proof Nash Equilibrium; Öffentliches Gut; Koalition; Interessenpolitik; Nash-Gleichgewicht; Agency Theory; Spieltheorie